The Impact of Dividend Payout Ratio, Leverage, and Profitability on Cash Holdings of Retail Companies Listed on the IDX from 2017 to 2023 - Rohmayati, Nita Selvia; Maghfiroh, Siti (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
The purpose of this study is to examine the simultaneous and partial effects of profitability, leverage, and dividend payout ratio on cash holdings in retailing companies that are listed on the Indonesia Stock Exchange between 2017 and 2023. This study employs a quantitative approach, using a purposive sampling strategy to select 12 organizations from a population of 43 companies. Descriptive statistics, multiple linear regression analysis, traditional assumption testing, and hypothesis testing were used in this study's data analysis. The study's findings concurrently demonstrate how cash holdings are impacted by the variables of profitability, leverage, and dividend payout ratio. According to the study's findings, retail businesses should concentrate on managing debt as best they can since it has been shown to impact their cash holdings. As a result, the business can maintain stable cash holdings.